Chronic Stresses in Resilient Urban Planning: Examining the Population-Amenity Balance Issue in Land Use Through the Case of Istanbul-Bağcılar - Tatar, Yunus; Dincer, Iclal Sema (KARE PUBL, 2025)
Cities can only be passed on to future generations if they are resilient to disasters. A critical factor influencing urban resilience is land use decisions. The size, density, and distribution of residential, commercial, and industrial areas, as well as the adequacy of green spaces and infrastructure, play a significant role in shaping resilience and quality of life. This article focuses on the Ba & gbreve;c & imath;lar district of Istanbul, analyzing whether urban resilience is achievable in densely populated areas with inadequate resources. Based on findings from the analysis, chronic stresses hindering urban resilience were identified, and recommendations were developed to address these challenges. As part of the field study, current land use patterns, transportation infrastructure, and the distribution of disaster assembly areas were examined. The aim was to evaluate the adequacy of existing amenities within land use plans in relation to population density. A detailed land use analysis was conducted at the neighborhood level to assess the capacity of existing facilities and infrastructure. Scenarios addressing the population-amenity balance were tested. Additionally, the adequacy of disaster assembly areas was analyzed, considering their spatial dimensions and compliance with standard criteria. Ba & gbreve;c & imath;lar's spatial planning history was reviewed using archival research and GIS mapping. Zoning plan amendments between 1986 and 2014 were analyzed manually, while post-2014 changes were examined via the e-plan automation system. These findings allowed inferences to be made regarding population density, land use changes, and mechanisms tied to the spatial planning culture. Proposed solutions are grounded in the legal framework of Article 18 of the Zoning Law No. 3194 (Land Readjustment Contribution Share). The study emphasizes Chronic Stresses Preventing Urban Resilience and aims to clarify factors impeding resilience. Furthermore, it tests urban resilience under existing and hypothetical scenarios, providing scientific contributions for future research.
Keywords: Disaster assembly areas; land use; urban resilience; urban amenity areas; spatial planning; CAPACITY; CHALLENGES; CLIMATE; WORLD; Public Administration